Mesenchymal stromal cells: facilitators of successful transplantation? - English, K; French, A; Wood, K (2010)
Mesenchymal stromal/stem cells (MSCs) possess immunomodulatory and reparative properties. Through specific interactions with immune cells that participate in both innate and adaptive responses, MSCs exposed to an inflammatory microenvironment can downregulate many immune effector functions. Clinical trials focusing on MSCs to treat graft-versus-host disease (GvHD) and autoimmune diseases are underway. Current analyses suggest that MSCs will improve cell and solid organ transplantation by ameliorating rejection and possibly eliminating the requirement for prolonged regimens of conventional immunosuppressive drugs. This review examines the in vitro and in vivo evidence for the clinical use of bone marrow derived MSCs.